Long-term athlete development (LTAD) strategy for optimizing movement skills and injury prevention in young athletes: literature review - Tomoliyus; Raya Puspita Wulan; Endang Rini Sukmawati; Abdul Alim (Indonesian Journal of Sport Management, 2025)
Background: The development of young athletes often faces issues related to short-term achievement orientation, early specialization practices, and the limited implementation of science-based approaches. Such conditions pose risks of recurring injuries, burnout, and suboptimal development of fundamental movement skills, which are essential as the foundation for long-term achievement. Long-Term Athlete Development (LTAD) emerges as a long-term athlete development model that emphasizes the alignment of training programs with the stages of growth, development, and biological maturity of young athletes. Purpose: to comprehensively examine LTAD strategies in optimizing movement skills while preventing injuries in young athletes. Methods: The research method used is a literature review by analyzing various scientific articles, research reports, and relevant sources discussing the implementation of LTAD, particularly related to fitness components such as strength, power, speed, agility, and aerobic fitness. Results: the integration of LTAD with training models such as resistance training and plyometric training has proven effective in improving fundamental movement skills, physical capacity, and reducing injury risk in young athletes. Furthermore, previous studies also emphasize that the application of LTAD can increase motivation, long-term participation in sports, and support the achievement of sustainable performance. Conclusion: LTAD is an important strategy in developing young athletes because it can optimize physical development, movement skills, and long-term health. Implications and Recommendation: coaches, sports practitioners, and development institutions need to implement LTAD systematically, adaptively, and with an orientation toward building healthy, resilient, and sustainable athletes.